Sengkalan dan Logika Pemikiran Orang Jawa - Suwito, Yuwono Sri (Kejawen, 2025)
Sengkalan (Javanese chronogram) is model years figur in Javanese culture. It is order to rending of years in the aesthetic sentences. Every word in Javanese culture have character numeral from zero to nine. In the Yogyakarta of Javanese prince in the principle consist of two form, there are lamba chronogram and memet chronogram. Reading strategy of chronogram from back to farward. All chronogram as history document very important. Chronogram especially lamba chronogram use commemoration event that paired at door, hose, etc. The name of numbering always used things, animal, ire, water, etc.